Effect of biofertilizer with reduced dose of nutrient solution on yield of Pak Choy on Nutrient Film Technique System - Hindersah, Reginawanti; Maulana, Nurzen; Damayani, Maya; Setiawati, Mieke Rochimi; Suryatmana, Pujawati; Fitriatin, Betty Natalie; Setiawan, Ade (Soilrens, 2023)
The Nutrient Film Technique (NFT) in hydroponic crop production systems generally uses chemical nutrient solutions to provide plant nutrients, even though biofertilizer inoculation can enrich liquid nutrients. The purpose of this experiment was to observe the effect of liquid biofertilizers applied with chemical nutrient solutions on changes in the acidity and electrical conductivity of nutrient solutions, as well as the growth and yields of pak choy (Brassica rapa L.) grown in Nutrient Film Technique. This experiment was set up in a completely randomized design with three nutrient solution treatments and eight replications. The treatments included the application of 100% chemical nutrient solution (control), and 75% and 50% concentrations of chemical nutrient solution enriched with a consortium biofertilizer. The results showed that at the end of the experiment, the acidity of all nutrient solutions increased, but their electrical conductivity (EC) was reduced. The fresh weight of pak choy shoots in medium B (75% chemical nutrition with biofertilizers) was 34% lower than the control (A), although statistically it was not significant. However, 50% chemical nutrition with biofertilizers produced the same shoot weight as the recommended dose of chemical nutrition. Moreover, 75% chemical nutrient with biofertilizers increased root weight. This current experiment verified that a reduced concentration of nutrient solution enriched with biofertilizer can be used to maintain the yield of pak choy grown in NFT.